Peran Zakat dalam Pengentasan Kemiskinan di Indonesia - Jufri Jacob; Mohammad Kotib; Muhammad Kamal; Ramli Semmawi; Fahmi Syam (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the role of zakat in alleviating poverty in Indonesia. This research uses a descriptive qualitative approach with content analysis techniques and library research. The research results show that zakat has an important role in reducing poverty rates in Indonesia. With professional management of zakat funds, it is possible to increase the level of demand and purchasing power of the community, so that the community becomes more prosperous. Apart from that, zakat funds are also able to increase investment activities and community productivity in business activities, so that in the end, professional management of zakat funds can reduce poverty rates.